Effect of Hot Water Treatment on Root-Knot Nematode, Meloidogyne incognita (Kofoid & White) Chitwood Infecting Tuberose (Polianthes tuberosa Linn.) Bulbs (Indian Journal of Nematology, 2024)
Three temperatures (45, 50, 55 0C) and time (15, 30, 45 min) combinations tested for hot-water treatment of root-knot nematode infected tuberose bulbs showed an improvement in plant growth and a good reduction of nematode population at all the treatments given at 500C. This temperature was more effective for 45 min treatment giving a reduction of 43, 36 and 57% in galls number, eggmasses number and soil population of nematode respectively. Hot water treatment given for 15 min at a temperature of 45 0C was not effective. A reduction of 26, 21 and 27 % in galls number, eggmasses number per plant and soil population of nematodes was obtained with hot-water treatment of 45 0C for 45 min. The bulbs were sensitive to hot water treatment of 55 0C given for 30 min or more. These treatments resulted in delayed establishment of the plant and the reduction in plant growth parameters of tuberose.